How diversification of overseas subsidiaries affects parent company innovation performance: evidence from China’s multinationals - Wang, Siyi; Chen, Xinni; Ye, Jinsong; Zhong, Changbiao (Frontiers in Psychology, 2024)
This paper examines the diversification of overseas subsidiaries on innovation performance of the parent company. Based on theoretical analysis and a combined Chinese firm dataset from 2000 to 2013, we find that diversification of overseas subsidiaries positively promotes the parent company innovation performance through the spillover effect of innovation capabilities. In addition, we determine that both the overseas and domestic investment layout can positively moderate the main effect. But there are differences between them. In concrete terms, the domestic investment layout plays a substitution effect in developed areas and acts a more pronounced moderating role in state-owned sample. Besides, the overseas investment layout plays a more important substitutive moderating role on non-state-owned enterprises. This research provides a special insight for studying the reverse spillover effect of OFDI in terms of the contribution of subsidiary linkages and offers several recommendations for multinational corporations to enhance the global competitiveness.